Cognitive profile of non-demented Parkinson's disease: Meta-analysis of domain and sex-specific deficits. (March 2019) - Curtis, Ashley F.; Masellis, Mario; Camicioli, Richard; Davidson, Heather; Tierney, Mary C.
Abstract: Introduction: Better awareness of the cognitive domains affected in non-demented Parkinson's Disease (PD) should improve understanding of cognitive disease mechanisms. A complete understanding of the cognitive areas impaired in non-demented PD is hindered because most studies use small clinical samples without comparison to healthy controls. This meta-analysis examined cumulative evidence across studies to determine if there were impairments in non-demented PD in the three cognitive domains thought to be most widely affected in PD: frontal executive, visuospatial, and verbal memory. Because there are well-documented sex differences in PD, a second objective was to explore sex differences in these findings. Methods: MEDLINE, EMBASE and PsycINFO databases were searched (1988–March 2017). Random effects models were used to compute and compare effect sizes of differences between PD patients and controls within cognitive domains. Sex differences in effect sizes were also examined in these comparisons. Moderating factors including age, disease duration, motor symptom severity, levodopa dosage, and depression were examined through meta-regression. Results: PD patients showed deficits of moderate effect sizes in all three cognitive domains relative to controls. Significant sex differences were observed only for frontal executive abilities, with male PD patients showing greater deficits than female PD patients relative to controls. No moderators of effect sizes were identified in the domain specific overall or sex-segregated meta-analyses. Conclusions: Results indicate that non-demented PD patients have deficits of moderate magnitude in frontal executive, verbal memory, and visuospatial abilities. Our findings of greater frontal executive deficits in males warrant further confirmation. Highlights: Cognitive areas impaired in non-demented PD relative to controls previously not well characterized. More men than women have PD, but sex differences in cognition have not been explored. Meta-analyses found moderate deficits in frontal executive, verbal memory, and visuospatial domains. Men showed significantly greater moderate deficits on frontal executive abilities.